Optimized distributed implementation of multiparty interactions with Restriction - Bensalem, Saddek; Bozga, Marius; Quilbeuf, Jean; Sifakis, Joseph (Science of computer programming, 2015)
Using high level coordination primitives allows enhanced expressiveness of component-based frameworks to cope with the inherent complexity of present-day systems designs. Nonetheless, their distributed implementation raises multiple issues, regarding both the correctness and the runtime performance of the final implementation. We propose a novel approach for distributed implementation of multiparty interactions subject to scheduling constraints expressed by priorities. We rely on a new composition operator named Restriction, whose semantics dynamically restricts the set of interactions allowed for execution, depending on the current state. We show that this operator provides a natural encoding for priorities. We provide a knowledge-based optimization that modifies the Restriction operator to avoid superfluous communication in the final implementation. We complete our framework through an enhanced conflict resolution protocol that natively implements Restriction. A prototype implementation allows us to compare performances of different optimizations.